TECHNICAL AND ECONOMIC JUSTIFICATION OF THE USE OF TURBULA TYPE-EQUIPMENT EQUIPMENT IN THE PERFORMANCE OF METAL DETAILS DEPARTMENT - ZALYUBOVSKYI, Mark; PANASYUK, Igor (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The types of shredding equipment used at domestic enterprises to perform the technological operation of separating parts from foundries are analyzed. It is established that machines with rotational movement of working tanks have low productivity of performance of these technological operations. In addition, a lot of time is spent on manual labor, in particular, reloading the working array to the vibrating screen. The design of the «Turbula» type galvanizing machine with complex spatial movement of the working capacity for the technological operation of separating metal parts from the foundries is proposed. This design of the machine is realized by combining in one design of the galvanizing tank (separation of parts from the foundries) and vibrating sieve (separation of separated parts from the foundries). Operation of such a structure allows to reduce the time spent on this technological operation, in particular, by providing convenient and unobstructed unloading of machined parts without the use of manual labor to overload the working array and further achieve separation of parts from foundries. The feasibility study for the use of «Turbula» equipment with complex spatial movement of the working capacity for the implementation of the technological operation of separating the metal parts of the "zipper" lock from the foundries was performed analytically. The expected annual economic effect from the introduction of the developed «Turbula» type machine with complex spatial movement of the working capacity to perform technological operations of separation of metal parts of the lock "lightning" from the foundries will be 25'688.7 UAH per unit of equipment. The developed design of the machine can be used for any type of parts (metal or polymer), which are formed by casting. The obtained research results can be used in the relevant design offices of machine-building enterprises at the stage of designing galvanizing equipment with complex spatial movement of working tanks.
Keywords: working capacity; separation; separation of parts from foundries; complex spatial movement